North Pillow Brings Bad Luck: Construction of Ideologies of English in a Japanese TV Drama, Massan. Issue 2 (3rd May 2020) - Ito, Rika
ABSTRACT: This article examines how ideologies of English are constructed and reproduced through the use of English by various television characters. It analyzes the form, content, and context in an NHK morning drama Massan, focusing on the construction of incompetence. Similar to previous studies, the contrast between characters based on their English skills are represented through various semiotic processes. However, unlike other studies where the individuals lacking English competence are represented as stupid and objects of ridicule, one of the main supporting characters of Massan uses 'bad English' but has a strong, positive role in the drama. The mismatch between the character's speech and her character in the drama seems to blur the negative aspect of incompetence in English, and possibly mollifies the viewers' own English inferiority complex. The juxtaposition of a strong supporting character with a lack of English creates a space for this alternative positive interpretation. However, such positive representation does not negate the power of English itself; rather, it appears to heighten the division among Japanese people based on their English skills.